Wegwijs in Avant-Garde Nu. (Turnhout : De Warande, 1984)
Boes, Dirk ; Claessens, Roger ; Croenen, Jan ; Daems, Walter (blad ontbreekt!) ; Govaerts, Jean-Paul ; Huybrechts, Jo ; Michielsen, Bart ; Riemis, Pool ; Teller, Christine ; Van Buggenhout, Chris ; Vandendriessche, Marc ; Van Den Heuvel, Cyriel ; Vandevelde, Ludwig (blad ontbreekt!) ; Vertessen, Liliane
Wegwijs in Avant-Garde Nu, De Warande, Turnhout, 1984
Nederlands
kunstcatalogus
Keywords: België